Answer:
not a factor
Step-by-step explanation:
If (x - 3) is a factor then f(3) = 0
f(x) = 2x² - 4x + 30
f(3) = 2(3)² - 4(3) + 30 = 18 - 12 + 30 = 36 ≠ 0
Since f(3) ≠ 0 then (x - 3) is not a factor of f(x)
<span>2x=4
Divide 2 on both sides so that the only thing remaining on the left side is the variable x.
Final Answer: x = 2</span>
Okay, to find length CE, your going to know the value of <em>x</em>. Length BC + CE = BD + DE.
3x+47+x+26=27+x+10
Simplify the equation to get
4x+73=37+x
you can choose one of four ways to continue, but I will choose to subtract x
3x+73=37
Subtract 73 from both sides of the equal sign
3x=-36
divide by 3 on both sides of the equal sign to get the value of x
x=-12
Now, plug in -12 for x in length CE to get -12+26=14
5 and 6 are true but 7 is not true. If you divide an odd number by 2 it's not going to be half of it